Response of potato vegetal and productive characters to foliar spray with Cycocel under water stress conditions - سليمان سوسن; دعيَس ماهر; حسن هادية (Latakia University Journal -Biological Sciences Series, 2021)
The effect of foliar spray with cycocel on potato vegetal and productive characters, under water stress conditions was studied, at Al- Hennadi research center, related to Agriculture research center – Lattakia- Syria. The research concluded 8 treatments : C40% (Control), CCC1000 , CCC1500, CCC2000 – C80% (Control), CCC1000 , CCC1500, CCC2000. The results showed that water stress reduced leaf area, plant height, leaf number, and productivity/ m2 . While, it did not affect small tuber number rate , neither medium and big, as well it did not affect small tuber weight rate, increased medium tuber weight rate, and reduced big tuber weight rate. The results showed as well that CCC treatment enhanced leaf area under water stress (40%), plant height at 1500 ppm, and leaf number at 1000 and 2000ppm. CCC treatment at 1000, 2000 ppm, increased leaf area, leaf number, and reduced plant height, at 80% of field capacity. CCC treatment as well, increased potato productivity at 40 and 80% of field capacity. and CCC at 1000, 2000 ppm. Increased number and weight of big tubers under water stress and normal conditions. CCC at 2000 ppm gave higher treatment efficiency under stress and normal conditions.